2005
DOI: 10.1111/j.1460-9592.2004.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Which may be effective to reduce blood loss after cardiac operations in cyanotic children: tranexamic acid, aprotinin or a combination?

Abstract: Our results suggested that both agents were effective to reduce postoperative blood loss and transfusion requirements in patients with cyanotic congenital heart disease. However, the combination of aprotinin and tranexamic acid did not seem more effective than either of the two drugs alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 17 publications
3
69
1
2
Order By: Relevance
“…They stated a nonsignificant trend of blood transfusion requirement decrease in the treated group compared with the placebo group during surgery and the postoperative period. 23 A few studies 13,16,17,20,23 have shown that intraoperative TXA administration led to less blood loss compared with a placebo group for different types of surgery. Nevertheless, some researchers 19,22 did not report a significant difference in blood loss using TXA or aprotinin, despite a significant decrease in total blood transfusion in the treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…They stated a nonsignificant trend of blood transfusion requirement decrease in the treated group compared with the placebo group during surgery and the postoperative period. 23 A few studies 13,16,17,20,23 have shown that intraoperative TXA administration led to less blood loss compared with a placebo group for different types of surgery. Nevertheless, some researchers 19,22 did not report a significant difference in blood loss using TXA or aprotinin, despite a significant decrease in total blood transfusion in the treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…even if a unique dose was sometimes administered before skin incision, 7,11,14 dosing schemes were usually based on a loading dose before incision and another dose in the CPB prime volume, in combination with a continuous infusion throughout surgery 7,9,10 or with another bolus at the end of CPB. [6][7][8]15 In addition, a significant variability between practitioners may be observed for each of those doses, as already illustrated with a 10-fold factor in the total dose (i.e., dose ranging from 30-300 mg/kg). 6,8 Some dosing schemes have been inspired from pharmacokinetic data in adults, 16 but the relevance of such an extrapolation may be questioned, because differences in the pharmacokinetics between adults and children undergoing cardiac surgery with CPB have already been reported.…”
Section: Pharmacokinetics Of Tranexamic Acid In Childrenmentioning
confidence: 92%
“…4 The use of antifibrinolytic drugs is one of the strategies for reducing blood loss, and tranexamic acid (TA) is among the most commonly administered, especially because the conclusions of the Blood Conservation Using Antifibrinolytics in a Randomized Trial study raised concerns about aprotinin. 5 The efficacy of TA in pediatric cardiac surgery has been demonstrated in several trials [6][7][8][9][10][11] and analyses, 12,13 but the determination of its dosage regimen …”
mentioning
confidence: 99%
“…There have been 11 comparative studies of lysine analogs in pediatric patients totaling >1000 patients. 147,[445][446][447][448][449][450][451][452][453][454][455] These are well described in a recent review and meta-analysis, and Table 7 summarizes the results of these studies. 445,456 These studies are of varying quality, and more than half of the patients have come from a single institution, the All-India Institute of Medical Sciences.…”
Section: Prevention and Treatment Of Postoperative Coagulopathymentioning
confidence: 99%